Enteral and supplemental parenteral nutrition enriched with omega-3 polyunsaturated fatty acids in intensive care patients – A randomized, controlled, double-blind clinical trial. Issue 5 (May 2021) - Singer, Pierre; Bendavid, Itai; Mesilati-Stahy, Ronit; Green, Pnina; Rigler, Merav; Lev, Shaul; Schif-Zuck, Sagie; Amiram, Ariel; Theilla, Miriam; Kagan, Ilya
Summary: Background & aims: Enteral nutrition (EN) and parenteral nutrition (PN) enriched with omega-3 polyunsaturated fatty acids (PUFA) have beneficial effects in critical illness. This study aimed to assess the combined effect of EN and supplemental PN enriched with omega-3 PUFA on blood oxygenation in intensive care unit (ICU) patients. Methods: Single-center, prospective, randomized, controlled, double-blind, phase III trial conducted from 10/2013 to 11/2017. A total of 100 ICU patients (18–85 years, APACHE II score > 15) requiring mechanical ventilation were randomly assigned to received combined EN and PN either with omega-3 PUFA (omega-3 group) or without (control group) for up to 28 days. Primary endpoint: 'change of PaO2 /FiO2 from day (D) 1 to D4'. Secondary endpoints: lung function parameters, ICU complications, length of hospital stay, days free of ICU care/ventilation/sedation/catecholamine treatment, mortality, erythrocyte fatty acid composition, inflammatory parameters. Safety parameters: standard laboratory assessment, vital signs, physical examination, SOFA score, adverse events. Results: Combined EN and PN covered energy requirements to more than 80%. Blood oxygenation (ΔPaO2 /FiO2 from D1 to D4: −1.3 ± 83.7, n = 42, and 13.3 ± 86.1, n = 39, in omega-3 and control group, respectively, p = 0.7795) and other lung function parameters did not differ between groups but days free of catecholamine treatment were significantly higher in the omega-3 group (~4 days, p = 0.0481). On D6, significantly more patients in the omega-3 group tolerated EN alone (51.0% vs. 29.8%, p = 0.0342). Eicosapentaenoic acid (EPA) content in erythrocytes was significantly increased in the omega-3 group at last observation compared with the control group (ΔEPA: 0.928 ± 0.808% vs. −0.024 ± 0.190%, p < 0.0001). No further significant group differences were detected. Conclusions: Enteral and supplemental PN both enriched with omega-3 PUFA did not improve lung function but allowed earlier weaning from catecholamine treatment and PN. Supplemental PN succeeded to adequately cover energy requirements in critically ill patients. Trial registration: www.clinicaltrials.gov, registration number: NCT01162928 .